PENGARUH SNOWBALL THROWING TERHADAP HASIL BELAJAR SISTEM PNEUMATIK KELAS X SMKN 1 BUNTOK - Riski Erai Kami; Wiyogo; Jhonni Rentas Duling (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2019)
The purpose of this study was to determine the effect of snowball throwing learning model on student learning outcomes in the basics of pneumatic system basics of automotive basic technology in class X of TSM SMKN 1 Buntok, year 2017/2018. This type of research uses true experimental design, the form of research design used in this study uses the form of the pretest-posttest type control group design wherein the initial test will be given before treatment is given and the final test will be given before treatment. The results of this study indicate that the calculation using the t test with a significance level of ? = 0.05 obtained a t count value of 10.25 while the t table value was 2.004. Because t count > t table. This means that H0 is rejected and H1 is accepted, so it can be concluded that there is an influence of student learning outcomes taught using the snowball throwing learning model